Robust aptamer–polydopamine-functionalized M-PLGA–TPGS nanoparticles for targeted delivery of docetaxel and enhanced cervical cancer therapy - Xu GJ (Dove Medical Press, 2016)
Guojun Xu,1–3,* Xinghua Yu,2,* Jinxie Zhang,1,2,* Yingchao Sheng,4 Gan Liu,2 Wei Tao,1,2 Lin Mei1,2 1School of Life Sciences, Tsinghua University, Beijing, 2Graduate School at Shenzhen, Tsinghua University, Shenzhen, 3School of Materials Science and Engineering, Tsinghua University, Beijing, 4Department of Orthopedic Surgery, Changshu Hospital of TCM, Changshu, People’s Republic of China *These authors contributed equally to this work Abstract: One limitation of current biodegradable polymeric nanoparticles (NPs) is the contradiction between functional modification and maintaining formerly excellent bioproperties with simple procedures. Here, we reported a robust aptamer–polydopamine-functionalized mannitol-functionalized poly(lactide-co-glycolide) (M-PLGA)–D-α-tocopheryl polyethylene glycol 1000 succinate (TPGS) nanoformulation (Apt-pD-NPs) for the delivery of docetaxel (DTX) with enhanced cervical cancer therapy effects. The novel DTX-loaded Apt-pD-NPs possess satisfactory advantages: 1) increased drug loading content and encapsulation efficiency induced by star-shaped copolymer M-PLGA–TPGS; 2) significant active targeting effect caused by conjugated AS1411 aptamers; and 3) excellent long-term compatibility by incorporation of TPGS. Therefore, with simple preparation procedures and excellent bioproperties, the new functionalized Apt-pD-NPs could maximally increase the local effective drug concentration on tumor sites, achieving enhanced treatment effectiveness and minimizing side effects. In a word, the robust DTX-loaded Apt-pD-NPs could be used as potential nanotherapeutics for cervical cancer treatment, and the aptamer–polydopamine modification strategy could be a promising method for active targeting of cancer therapy with simple procedures. Keywords: dopamine, AS1411 aptamer, active targeting, polymeric NPs, enhanced cervical chemotherapy